1993
DOI: 10.1577/1548-8659(1993)122<0616:mobtms>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of Brook Trout, Mottled Sculpins, and Slimy Sculpins during Acidic Episodes

Abstract: Brook trout Salvelinusfontinalis. mottled sculpins Cottus bairdi. and slimy sculpins Cottus cognatus occur in many Pennsylvania streams that have depressed pH and elevated aluminum concentrations during episodes of high stream discharge (acidic episodes). We performed 20-d in situ cage exposures with these species to determine their relative sensitivities to field conditions. We also exposed fish in the laboratory to synthetic soft water, without added Al, to elevate possible effects of Al on sodium flux rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 18 publications
1
32
0
Order By: Relevance
“…No acid-tolerance information is available for the longnose dace, but its distribution in the Neversink River indicates that it is more acid tolerant than blacknose dace and as tolerant as brown trout. Though pH tolerance levels offer a general ranking of each species' sensitivity in acidified systems, many studies have shown that other factors such as Al im , DOC, and Ca 2+ , along with the timing and magnitude of episodic fluctuations in toxic acid and Al im concentrations, are strongly related to the degree of stream acidification and influence fish survival in natural systems (Baker et al, 1990;Gagen et al, 1993;Simonin et al, 1993;Van Sickle et al, 1996;Baldigo and Murdoch, 1997). Aluminum fractionation and Al im concentration are also directly dependent upon pH levels (Driscoll, 1985) and both acidity and Al im act in a similar manner to affect fish survival (Wood et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…No acid-tolerance information is available for the longnose dace, but its distribution in the Neversink River indicates that it is more acid tolerant than blacknose dace and as tolerant as brown trout. Though pH tolerance levels offer a general ranking of each species' sensitivity in acidified systems, many studies have shown that other factors such as Al im , DOC, and Ca 2+ , along with the timing and magnitude of episodic fluctuations in toxic acid and Al im concentrations, are strongly related to the degree of stream acidification and influence fish survival in natural systems (Baker et al, 1990;Gagen et al, 1993;Simonin et al, 1993;Van Sickle et al, 1996;Baldigo and Murdoch, 1997). Aluminum fractionation and Al im concentration are also directly dependent upon pH levels (Driscoll, 1985) and both acidity and Al im act in a similar manner to affect fish survival (Wood et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…These values occur naturally in many soils and are increasingly common because of widespread acidification associated with acid precipitation (42). Acidification clearly mobilizes aluminum and has been associated with significant impacts on plant and animal populations (7,16,48). Whether microbial processes in soils are similarly affected is not certain.…”
mentioning
confidence: 99%
“…Second, causation cannot be directly inferred from a correlation without a clear mechanism. For stream pH, numerous lab studies (Ingersoll et al 1990;Mount et al 1990;Cleveland et al 1991;Jagoe and Haines 1997) and field bioassay studies (Gagen et al 1993;Simonin et al 1993;Baker et al 1996;Van Sickle et al 1996;Baldigo and Murdoch 1997;Lachance et al 2000) increase our confidence that low pH and associated dissolution of monomeric aluminum (Al +3 ) influence fish biomass in headwater streams. As noted above, the association of pool habitat with fish biomass has been documented in other correlative studies (Stichert et al 2001;Binns 2004;Harvey et al 2005;Young et al 2005).…”
Section: Discussionmentioning
confidence: 99%